A Conceptual Framework of Green Supply Chain Management for Manufacturing Firms - Tonmoy Kumar Das; Wahidul Sheikh; Nahidul Islam; Abu Bakar Siddik (International Journal of Supply Chain Management, 2021)
The need for adopting environment-friendly strategies is echoing all over the world. Everyone now is concern about the detrimental effects of environmental pollution from industrialization and excessive carbon emission for producing goods and services by large corporations. Business leaders are looking for ways forward to get rid of it. In this aspect, green supply chain management (GSCM) can play a vital role by obviating the environmental wastes along with the chain and ensuring the best use of resources that will eventually be financially beneficial for the firms also. This study aims at drawing a conceptual framework of green supply chain management and finding out the influential factors of the GSCM in the manufacturing firms in Bangladesh. The study is an exploratory research based on secondary data. Based on a rigorous review of the existing literature, a conceptual framework has been prepared and various factors of GSCM have been identified in the context of Bangladesh. A model of GSCM has been proposed for the manufacturing firms in the socio-economic condition of Bangladesh.